Effect Biomarkers of the Widespread Antimicrobial Triclosan in a Marine Model Diatom - Bernardo Duarte; Eduardo Feijão; Ricardo Cruz de Carvalho; Ana Rita Matos; Maria Teresa Cabrita; Sara C. Novais; Ariana Moutinho; Marco F. L. Lemos; João Carlos Marques; Isabel Caçador; Patrick Reis-Santos; Vanessa F. Fonseca (MDPI AG, 2022)
The present-day COVID-19 pandemic has led to the increasing daily use of antimicrobials worldwide. Triclosan is a manmade disinfectant chemical used in several consumer healthcare products, and thus frequently detected in surface waters. In the present work, we aimed to evaluate the effect of triclosan on diatom cell photophysiology, fatty acid profiles, and oxidative stress biomarkers, using the diatom Phaeodactylum tricornutum as a model organism. Several photochemical effects were observed, such as the lower ability of the photosystems to efficiently trap light energy. A severe depletion of fucoxanthin under triclosan application was also evident, pointing to potential use of carotenoid as reactive oxygen species scavengers. It was also observed an evident favouring of the peroxidase activity to detriment of the SOD activity, indicating that superoxide anion is not efficiently metabolized. High triclosan exposure induced high cellular energy allocation, directly linked with an increase in the energy assigned to vital functions, enabling cells to maintain the growth rates upon triclosan exposure. Oxidative stress traits were found to be the most efficient biomarkers as promising tools for triclosan ecotoxicological assessments. Overall, the increasing use of triclosan will lead to significant effects on the diatom photochemical and oxidative stress levels, compromising key roles of diatoms in the marine system.